Microcontroller-Based Mechanics Experiments in Physics Learning: Systematic Literature Review Using PRISMA - Fauza, Naila; Ernidawati, Ernidawati; Zulhelmi, Zulhelmi; Rahim, Fanny Rahmatina; Riwandi, Fayolla Octa; Latif, Ahmad Amirul; Mathluba, Khairan (Jurnal Penelitian Pendidikan IPA, 2023)
Microcontrollers are capable of digitizing conventional equipment so that it will make it easier for practitioners to carry out experiments. The aim of this research is to determine the use of microcontrollers in physical mechanics experiments using the Systematic Literature Review method. The data collected was in the form of national and international journal articles from accredited and indexed electronic databases and then extracted. The research results show mechanical experiments using microcontroller-based experimental tools, supporting sensors used in these tools, the learning models applied, learning achievements that can result from activities and the types of research used to discuss these experimental tools